Development and benchmarking of a Monte Carlo dose engine for proton radiation therapy - Lysakovski, Peter; Ferrari, Alfredo; Tessonnier, Thomas; Besuglow, Judith; Kopp, Benedikt; Mein, Stewart; Haberer, Thomas; Debus, Jürgen; Mairani, Andrea (Frontiers in physics, 2021)
Dose calculation algorithms based on Monte Carlo (MC) simulations play a crucial role in radiotherapy. Here, the development and benchmarking of a novel MC dose engine, MonteRay, is presented for proton therapy aiming to support clinical activity at the Heidelberg Ion Beam Therapy center (HIT) and the development of MRI (magnetic resonance imaging)-guided particle therapy. Comparisons against dosimetric data and gold standard MC FLUKA calculations at different levels of complexity, ranging from single pencil beams in water to patient plans, showed high levels of agreement, validating the physical approach implemented in the dose engine. Additionally, MonteRay has been found to match satisfactorily to FLUKA dose predictions in magnetic fields both in homogeneous and heterogeneous scenarios advocating its use for future MRI-guided proton therapy applications. Benchmarked on 150 MeV protons transported on a 2 x 2 x 2 mm3 grid, MonteRay achieved a high computational throughput and was able to simulate the histories of more than 30 000 primary protons per second on a single CPU core.
Gesehen am 16.12.2021